Pengaruh Limbah Sampah di Sungai Beldang Kota Kalabahi - Paulina S. Padafing; Melki Imamastri Puling Tang; Imanuel Yosafat Hadi Manapa; Nehemia Fanpada; Yanti Th. Tangbay; Trisanti A, Lema; Yenny S. Telly; Vantica P. Ou’w; Julminggu J. Selly (Lembaga Pengembangan Kinerja Dosen, 2023)
Kali beldang is one of the areas located in Teluk Mutiara District, Alor Regency East Nusa Tenggara. This time it was one of the times that looked very dirty. There is a lot of garbage scattered around the river, even in the water stream. There are various kinds of waste, ranging from garbage, waste from animal feed disposal, livestock manure, waste in the form of torn cloths, to plastic waste that is very difficult to decompose and Masi many more hazardous waste that cannot be recycled. This research will be carried out with qualitative methods as research observation, with the aim of the researcher, The qualitative approach is to observe, explain, describe, describe critically.